Scattering by a 2D Crack: The Meshfree Collocation Approach - Honarbakhsh, B.; Tavakoli, A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, the meshfree collocation method is applied to the problem of EM scattering by a 2D crack in a PEC plane. The hybrid PDE-IE formulation is the mathematical statement of the problem. Consequently, the geometry and the filling material of the cavity is arbitrary. Validations are based on convergence analysis, modal solution and measurement results. Furthermore, elliminating numerical integrations has lead to a fast, accurate, and general meshfree solution.